Lemierre's Syndrome: A Rare Case of Pulmonic Valve Vegetation. (21st March 2013) - Kwan, Clara; Mastrine, Lou; Moskovits, Manfred
Abstract : Lemierre's syndrome is an uncommon complication of pharyngitis commonly associated with an anaerobic gram negative bacterium, Fusobacterium necrophorum . The syndrome usually affects young healthy adults with the mean age of 20 and is characterized by recent pharyngitis followed by ipsilateral internal jugular vein thrombosis and septic thromboembolism. The treatment is at least 6 weeks of antibiotics; the role of anticoagulation is unclear. The following presentation is a case of Lemierre's syndrome in a 23-year-old healthy individual who is infected by a rare species: Fusobacterium nucleatum . The case is complicated by septic emboli to the lungs and impressive seeding vegetation to the right ventricular outflow tract (RVOT) at the pulmonic valve of the heart.